Catalytic effects of CeO2 and carbon nanotube addition in plasma-sprayed Al2O3. Issue 1 (14th June 2017) - Banerjee, Amitava; Mahato, Neelima; Bhaduri, Bhaskar; Balaji, Narayanaswamy; Siddiqui, Abdul Rahim; Aruna, Singanahalli ThippaReddy; Verma, Nishith; Balani, Kantesh
Abstract : Ceramic composite coatings of alumina (Al2 O3 ), alumina–micro-ceria (µ-CeO2 ) and alumina–micro-ceria–multiwalled carbon nanotubes (MWNTs) were processed using plasma spraying. X-ray diffraction analysis reveals evolution of new phases – namely, γ-alumina and non-stoichiometric phases of alumina. Reinforcement of 3 wt% MWNTs has been shown to restrict the degeneration of ceria and synergistically conserve the γ-phase. The catalytic ability of alumina–micro-ceria–MWNT has been confirmed from the nitric oxide (NO) oxidation reaction. An observed 25% conversion ability arises at 350°C in a 10% oxygen (O2 ) environment, which indicates that ceria inclusion increases the oxidation of nitric oxide. Thus, the alumina–micro-ceria–MWNT composite can serve as a potential catalyst for nitric oxide conversion.